1981
DOI: 10.1002/hep.1840010502
|View full text |Cite
|
Sign up to set email alerts
|

A controlled clinical trial of the efficacy of the hepatitis B vaccine (heptavax B): A final report

Abstract: A controlled, randomized, double-blind trial in 1,083 homosexual men from New York confirmed that a highly purified, formalin-inactivated vaccine against hepatitis B prepared from HBsAg positive plasma, is safe immunogenic, and highly efficacious. Over 95% of vaccinated subjects developed antibody against the surface antigen. Vaccine-induced antibody persisted for the entire 24-month follow-up period. The attack rate of all hepatitis B virus infections (excluding conversions of anti-HBc alone) was 3.2% in vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
0
3

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(136 citation statements)
references
References 13 publications
6
127
0
3
Order By: Relevance
“…Other side effects were a rash at the injection site, pruritus and temperature elevations, which were seen in a few cases only. Thus it can be concluded that the vaccine is safe and the adverse effects are similar to those after application of other vaccine preparations [22,23,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other side effects were a rash at the injection site, pruritus and temperature elevations, which were seen in a few cases only. Thus it can be concluded that the vaccine is safe and the adverse effects are similar to those after application of other vaccine preparations [22,23,27].…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Szmuness et al [21,22], Maupas et al [12], Crosnier et al [2,3], and ReerinkBrongers et al [18] demonstrated the safety and efficacy of active immunization against hepatitis B in homosexuals, children in Senegal, hemodialysis unit staff and patients, and volunteers. These populations are not only at high risk as far as morbidity and mortality of the acute illness is concerned, but also because of chronic viral hepatitis, liver cirrhosis, and primary liver cell carcinomaconditions which to date cannot be treated effectively.…”
mentioning
confidence: 99%
“…GMTs for anti-HBs levels in each age group at 1 and 12 months were 402.08 (330. 13 (16.88, 37.29) mIU/ml, respectively. Apart from the seroconversion rate at 1 month (p > 0.05), significant differences were identified of the sero-protective rate at 12 months and…”
Section: Immunogenicity-related Factorsmentioning
confidence: 95%
“…This vaccine has been widely used all over the world with considerable success. It has proved to be highly effective in preventing infection, especially in healthy individuals with a minimum of side effects [1]. Non-responsiveness to the vaccine is more prevalent in individuals with some degree of immunodeficiency, but even this problem can often be overcome by increasing the dose.…”
Section: Introductionmentioning
confidence: 99%